Polygamy: Uncovering the effect of patriarchal ideology on gender-biased interpretation - Hasan, Hamka (HTS teologiese studies, 2022)
Polygamy, which was practiced without limitations in the past, had been restricted to four wives after the arrival of Islam in the Arabian Peninsula. However, some scholars have different views on this issue, supposedly influenced by the literal and cultural background of patriarchal tradition on treating women as the object of polygamy. This article attempts to examine the construction of patriarchal interpretation in a gender-biased interpretation, its factors and its implications. This study adopts a qualitative approach and employs a content analysis approach. Interviews with relevant scholars are also used to explore in-depth information regarding this subject. The object of research is based on a full set (30 juz/chapters) of 11 books of tafsir written in Indonesia. These books are Tafsir Al-Furqan, Tafsir Quran, Adz-Dzikra: Terjemah dan Tafsir al-Quran, Al-Quran dan Terjemahnya, Tafsir Quran Karim, Tafsir al-Azhar, Tafsir Rahmat, Tafsir al-Quran al-Majid an-Nur, Tafsir al-Mishbah, Al-Quran and its Exegesis of the Department of Religion, and Tafsir al-Hijri. This study found that women have been exploited through polygamy practices. Our findings show that biased gender interpretation, especially because of the patriarchal mindset, brought a greater impact on the Quranic interpretation. This study suggested that reinterpretation towards Quranic verses particularly dealing with gender issues needs to be strengthened in accordance with justice and humanistic values.Contribution: This article offered two approaches for the study of the Quran in order to establish gender equality and justice in marriage practice. Firstly, the adaptive and humanistic interpretations of the Quran need to be strengthened and should raise common consciousness in Muslim society. Secondly, there is a need to study the Quran in an integrative, holistic and hermeneutical understanding of the Quranic text. This method can explore the deepest meaning of the Quran so it can rise gender-sensitive, humanist and moderate interpretations.